Molecular Monitoring in Acute Myeloid Leukemia Patients Undergoing Matched Unrelated Donor - Hematopoietic Stem Cell Transplantation: Single Center Experience - Irina Panovska-Stavridis; Aleksandra Pivkova-Veljanovska; Sanja Trajkova; Ridova, Nevenka; Zlate Stojanoski; Lazar Cadievski; Marija Popova-Labachevska; Nadica Matevska-Geshkovska; Lidija Cevreska; Borche Georgievski; Aleksandar Dimovski (Macedonian Academy of Sciences and Arts / Sciendo, 2020)
Introduction: Minimal residual disease (MRD) assessment in acute myeloid leukemia (AML) cases is a complex, multi-modality process and, though much of its clinical implications at different points are extensively studied, it remains even now a challenging area. It is a disease the biology of which governs the modality of MRD assessment; in patients harboring specific molecular targets, high sensitivity techniques can be applied. On the other hand, relapse is considered as the leading cause of treatment failure in AML patients undergoing allogeneic hematopoietic stem cell transplantation (alloHSCT). Materials and methods: Since November 2018 until June 2020, 10 AML patients underwent matched unrelated donor (MUD) HSCT at the University Clinic of Hematology-Skopje, Republic of North Macedonia. Molecular markers were identified in a total of 4 patients; 3 patients expressed chimeric fusion transcripts; two RUNX-RUNX1T1 and one for CBFB-MYH11. One patient harbored mutation in the transcription factor CCAAT/enhancer binding protein α (CEBPA). Post-transplant MRD kinetics was evaluated by using quantitative polymerase chain reaction (RT-qPCR) or multiplex fluorescent-PCR every three months during the first two years after the transplantation. Results: MRD negativity was achieved in three pre-transplant MRD positive patients by the sixth month of HSCT. They sustained hematological and molecular remission for 19, 9 and 7 months, respectively. The fourth patient died due to transplant-related complications. Conclusion: According to our experience, when molecularly-defined AML patients undergo HSCT, regular MRD monitoring helps predict impending relapse and direct future treatment strategies.
Keywords: CBFB-MYH11; CEBPA; acute myeloid leukemia (AML); matched unrelated donor (MUD); minimal residual disease (MRD); molecular monitoring; hematopoietic stem cell transplantation (HSCT); RUNX-RUNX1T1